2015
DOI: 10.1186/s40064-015-1607-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of extubation failure in newborns, infants and children: brief report of a prospective (blinded) cohort study at a tertiary care paediatric centre in India

Abstract: BackgroundExtubation failure (EF), defined as need for re-intubation within 24–72 h, is multifactorial. Factors predicting EF in adults generally are not useful in children.ObjectiveTo determine the factors associated with EF and to facilitate prediction of EF in mechanically ventilated infants and children less than 12 years of age.Material and MethodsDesign Prospective cohort study. Setting PICU and NICU of a multispecialty tertiary care institute. Patients All consecutive newborns, infants and children, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
8
0
4
Order By: Relevance
“…This similar study revealed no association between the RSBI measurements and extubation outcomes [ 20 ]. In other studies about pediatric patients in general, they found an association between the measurements of RSBI prior to extubation and the extubation outcomes which is a prediction of extubation success with low RSBI similar to the results in the two hours prior to extubation RSBI measurements in our study [ 9 , 10 , 22 , 23 ]. Unlike our study, some of these studies established a threshold, cut-off point, to predict the successful extubation, but these cut-off points were variable and ranging from 6.7 to 11 [ 9 , 10 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…This similar study revealed no association between the RSBI measurements and extubation outcomes [ 20 ]. In other studies about pediatric patients in general, they found an association between the measurements of RSBI prior to extubation and the extubation outcomes which is a prediction of extubation success with low RSBI similar to the results in the two hours prior to extubation RSBI measurements in our study [ 9 , 10 , 22 , 23 ]. Unlike our study, some of these studies established a threshold, cut-off point, to predict the successful extubation, but these cut-off points were variable and ranging from 6.7 to 11 [ 9 , 10 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…We read with interest the study on a quality improvement (QI) initiative for extubation in newborns [1]. Failed extubation is a common problem faced by healthcare workers across all neonatal intensive care units [2,3] and a QI initiative designed to improve this is a welcome step. We have two observations regarding this reasonably wellconducted study.…”
Section: Protocol Driven Extubation In Neonates-a Quality Improvementmentioning
confidence: 99%
“…However, these parameters were predominantly used in research and not in a clinical setting ( 9 ). Moreover, some of these parameters have proven helpful in adults but are not generally used in children ( 10 ). The occlusion pressure (P0.1) is the decrease in airway pressure 100 ms after occluded inspiration ( 11 ).…”
Section: Introductionmentioning
confidence: 99%